PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAPPENGUNGKAPAN AKUNTANSI SUMBER DAYA MANUSIA(STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSAEFEK INDONESIA TAHUN 2015) - WIDADPUTRA SUDRAJAT, HILLAN (Jurnal Akuntansi AKUNESA, 2017)
This study aims to analyze the influence of corporate characteristics against thedisclosure of human resource accounting (empirical study on companies listed inIndonesia Stock Exchange in 2015). Of all 537 populations, 371 firms listed onthe Indonesia Stock Exchange were selected as research samples in 2015. Thedata used in this research are annual reports, which have been published inIndonesia Stock Exchange. Data analysis used ini testing company size,profitability and age of company to disclosure of human resource accounting ismultiple linier regression analysis. The results of this study indicate that the sizeof company affect the disclosure of human resource accounting, profitability doesnot affect the disclosure of human resource accounting, age of the company doesnot affect the disclosure of human resource accounting. Keywords: company size, profitability, company age, human resource accountingdisclosure.